Animal models of mucositis: critical tools for advancing pathobiological understanding and identifying therapeutic targets. Issue 2 (June 2019) - Wardill, Hannah R.; Tissing, Wim J.E.; Kissow, Hannelouise; Stringer, Andrea M.
Abstract : Purpose of review: Mucositis remains a prevalent, yet poorly managed side effect of anticancer therapies. Mucositis affecting both the oral cavity and gastrointestinal tract predispose to infection and require extensive supportive management, contributing to the growing economic burden associated with cancer care. Animal models remain a critical aspect of mucositis research, providing novel insights into its pathogenesis and revealing therapeutic targets. The current review aims to provide a comprehensive overview of the current animal models used in mucositis research. Recent findings: A wide variety of animal models of mucositis exist highlighting the highly heterogenous landscape of supportive oncology and the unique cytotoxic mechanisms of different anticancer agents. Golden Syrian hamsters remain the gold-standard species for investigation of oral mucositis induced by single dose and fractionated radiation as well as chemoradiation. There is no universally accepted gold-standard model for the study of gastrointestinal mucositis, with rats, mice, pigs and dogs all offering unique perspectives on its pathobiology. Summary: Animal models are a critical aspect of mucositis research, providing unprecedent insight into the pathobiology of mucositis. Introduction of tumour-bearing models, cyclic dosing scheduled, concomitant agents and genetically modified animals have been integral in refining our understanding of mucositis.